2012
DOI: 10.1002/cphc.201100852
|View full text |Cite
|
Sign up to set email alerts
|

Density, Thermal Expansion and Viscosity of Cholinium‐Derived Ionic Liquids

Abstract: Density and viscosity data of the N-alkyl-N,N-dimethyl-N-(2-hydroxyethyl)ammonium bis(trifluoromethylsulfonyl)imide ionic liquids homologous series [N(1 1 n 2(OH))][Ntf(2)] with n=1, 2, 3, 4 and 5 have been measured at atmospheric pressure in the 283 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 78 publications
5
58
0
1
Order By: Relevance
“…The density increase of the binary samples with nucleobase concentration is shown in Figure 4. This fact can probably be attributed to the strong interactions between the solute and the ionic liquid [41], which agrees with the strong hydrogen bonding between the nucleobases and both the IL anion and cation, determined by NMR spectroscopy in a previous study concerning the dissolution mechanism of nucleobases in 1,3-dialkylimidazolium acetate ILs [8]. We have also observed similar phenomena of increasing density with the solute concentration when mixtures of ionic liquids and simple inorganic salts were studied [42].…”
Section: Binary Systemssupporting
confidence: 78%
See 1 more Smart Citation
“…The density increase of the binary samples with nucleobase concentration is shown in Figure 4. This fact can probably be attributed to the strong interactions between the solute and the ionic liquid [41], which agrees with the strong hydrogen bonding between the nucleobases and both the IL anion and cation, determined by NMR spectroscopy in a previous study concerning the dissolution mechanism of nucleobases in 1,3-dialkylimidazolium acetate ILs [8]. We have also observed similar phenomena of increasing density with the solute concentration when mixtures of ionic liquids and simple inorganic salts were studied [42].…”
Section: Binary Systemssupporting
confidence: 78%
“…It has already been shown that, despite the highly complex liquid structure of ILs, their volumetric properties behave very near to ideality. Thus, the ILs volume can be taken as the sum of the effective volumes of the constituent cations and anions (V m = V ⁄ c + V ⁄ a ), which have been well defined in the literature [38][39][40][41]. Although the typical predictive power of this algorithm is better than 0.5%, the calculated molar volumes of [ As it is well known, dynamic viscosity is more sensitive to impurities than density and the deviations found between our results and the literature values illustrate exactly this fact, as depicted in figure 2(a) and (b).…”
Section: Pure Ionic Liquidsmentioning
confidence: 99%
“…This fact can probably be attributed to the more exposed charge of imidazolium cation when compared to that of the tetraalkylammonium cation, where the charge is more hidden due to the presence of four hydrocarbon chains as well as the presence of an acidic proton H-2 from imidazolium cation. These structural differences in terms of the charge accessibility have already been observed by molecular dynamics and used to interpret other phenomena (Blesic et al, 2010;Costa et al, 2012;Marcelino et al, 2007).…”
Section: Water Solubility and Octanol-water Partition Coefficientmentioning
confidence: 68%
“…for density, thermal expansion and viscosity of cholinium-derived ionic liquids (Costa et al, 2011;Costa et al, 2012), viscosity (Adamová et al, 2011, the glass-transition temperature and fragility (Gacino et al, 2011), experimental data of mixture with ionic liquid were compared with group contribution methods (Cehreli & Gmehling, 2010) or thermophysical properties were studied (Gardas et al, 2010).…”
Section: X(c-h) and X(o-h)mentioning
confidence: 99%